ANALISI KECELAKAAN LALU LINTAS PADAsJALAN TJILIKfRIWUT KOTA PALANGKA RAYA - Oktaviani, Aria Resti; Elvina, Ina; Robby, Robby (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
Tjilik Riwut Street, Palangka Raya city, is a road with quite dense traffic, so that it can cause traffic problems, especially traffic accidents. This study aims to determine the level of traffic accidents on the Tjilik Riwut road Kms0+000dto Kms12+000dPalangkasRaya City and the areas where accidents often occur, the time of the accident and the cause of the accident. Thus it will be known what efforts cansbe madesto overcome the accident that occurred. The approachbusedfin thisfresearch is descriptive percentage analysis which is the process of describing the research location. The results of the study, it was obtained that the accident rate in 2018 was 22 accidents, in 2019 there were 35 accidents, in 2020 there were 25 accidents, in 2021 there were 34 accidents and in 2022 there were 39 accidents. Points that often occur accidents are at Km 1, Km 5, Km 8 and Km 10. Factors causing accidents in accident-prone areas on the Tjilik Riwut Km 2 road in Palangka Raya city are due to driver conditions (91%), road and environmental conditions (9%) and vehicle damage (0%). The most frequent accident time is between 06.00 – 12.00 WIB (33%). Double accidents are the most common type of accident (73%). Accidents often occur at the age of 21-30 years (27%).